The Effect of Audit Partner’s Perceptions of Locus of Control, Organizational Commitmnet and Audit Fee on Audit Quality - Rusmawan Wahyu Anggoro ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2022)
This study examines the effect of locus of control, organizational commitment and audit fees on audit quality from the audit partner's point of view. Attribution theory and agency theory are used to develop hypotheses and analyze the effect of each variable on audit quality. Data collection in this study used purposive sampling with the criteria of KAP partner participants registered with the Indonesian Institute of Certified Public Accountants (IAPI). 246 participants from 477 partners registered in the IAPI directory obtained, 195 of them met the requirements of the study. Smart partial least square (Smart-PLS) was used to analyze the data. Additional testing using SPSS was carried out to see the consistency of the results and increase confidence in the results of the analysis. The results of this study indicate that audit quality is influenced by locus of control, while organizational commitment and audit fees are not. Discussion and elaboration using the IAPI code of ethics and auditing standards enrich the explanation of the research results.